Pengaruh Environmental, Social, and Governance Disclosure (ESGD) pada Nilai Perusahaan: Peran Ukuran Perusahaan sebagai Variabel Moderasi - Sri Eka Noviyanti; Adi Wiratno (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aimed to analyze the effect of Environmental, Social, and Governance Disclosure (ESGD) on firm value by considering firm size as a moderating variable. The research method used was quantitative. The type of data in this study was secondary data, namely annual reports and sustainability reports of mining companies for the 2021–2023 period. The sampling technique was carried out through a purposive sampling method, resulting in a total of 81 company data were obtained for the sample. The data were analyzed using SPSS 26. The results of the study showed that ESGD had a negative effect on firm value due to high costs that reduced profitability, leading investors who prioritized short-term profits to consider it a negative signal and lose trust. In addition, the results also showed that firm size strengthened the relationship between ESGD and firm value because large companies have adequate financial resources, are able to handle the complexity of ESG implementation, and had high visibility to attract stakeholder support.